Sztab planowania polityki departamentu stanu - Rak, Wiktor (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2011)
This paper demonstrates the most formidable challenges that the Policy Planning Staff in the Department of State has been facing since it was created in 1947 by G. Marshall and G. Kennan. In the first place attention is paid to the history of this institution. The following turning points were identified: the creation under G. Kennan and the incumbency of H. Kissinger as a Secretary of State. Then there are debated a few most important issues which the Policy Planning Staff deals with. It comprises difficulties in exerting influence, impossibility of merging the focus on strategic thinking with operational disposability. Finally, in the article there are presented some ideas of Z. Brzezinski who sought to enhance the Staff’s performance. The intention of this article is to shed light on the obstacles that the policy planners have to tackle in order to effectively impact the American foreign policy. This issue has not been exhaustively discussed yet in the Polish scientific literature.